2000
DOI: 10.1001/jama.284.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and Virologic Effects of Subcutaneous Interleukin 2 in Combination With Antiretroviral Therapy

Abstract: Intermittent therapy with IL-2 and ART produced a substantially greater increase in CD4 cells and was associated with a larger decrease in viral load than ART alone. Clinical end-point trials will be necessary to determine whether the enhanced viral suppression and CD4 cell increases associated with IL-2 therapy will translate into improved clinical outcomes. JAMA. 2000;284:183-189

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 162 publications
(79 citation statements)
references
References 20 publications
(19 reference statements)
5
73
0
1
Order By: Relevance
“…Multiple randomized trials have demonstrated that the administration of intermittent cycles of IL-2 to HIV-infected patients can lead to profound, sustained increases (often greater than 100%) in CD4 cell number and percentage (1)(2)(3). After 3 to 6 five-day cycles of IL-2 administered every 2 months, CD4 cell numbers may remain elevated for years without additional cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple randomized trials have demonstrated that the administration of intermittent cycles of IL-2 to HIV-infected patients can lead to profound, sustained increases (often greater than 100%) in CD4 cell number and percentage (1)(2)(3). After 3 to 6 five-day cycles of IL-2 administered every 2 months, CD4 cell numbers may remain elevated for years without additional cycles.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The initial induction regimen consists of 5-day cycles that are administered every 8 weeks for 3 to 6 cycles. The majority of treated patients then require only infrequent cycling for maintenance of these CD4 expansions.…”
Section: Introductionmentioning
confidence: 99%
“…The CD45RO ϩ CD4 ϩ memory T cells appear to harbor the majority of the latent virus. To date, several approaches have been aimed at eliminating these cells (9,(25)(26)(27)(28)(29), but none have been highly successful (29)(30)(31). Another proposed strategy involves the use of HIVbased vaccines to stimulate anti-HIV cytotoxic T lymphocytes, which might recognize and eliminate the latent reservoir (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…However, even after years with viremia below the limit of quantitation (BLQ), the frequency of these infected cells does not decrease further (1,4,6,7). The therapeutic approaches evaluated to date have failed to demonstrate a significant and persistent decline of this latent viral reservoir (8,9).…”
mentioning
confidence: 99%